2020
DOI: 10.3390/ijms21051878
|View full text |Cite
|
Sign up to set email alerts
|

TmSpz4 Plays an Important Role in Regulating the Production of Antimicrobial Peptides in Response to Escherichia coli and Candida albicans Infections

Abstract: Spätzle family proteins activate the Toll pathway and induce antimicrobial peptide (AMP) production against microbial infections. However, the functional importance of Tmspätzle4 (TmSpz4) in the immune response of Tenebrio molitor has not been reported. Therefore, here, we have identified and functionally characterized the role of TmSpz4 against bacterial and fungal infections. We showed that TmSpz4 expression was significantly induced in hemocytes at 6 h post-injection with Escherichia coli, Staphylococcus au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
(59 reference statements)
4
21
0
1
Order By: Relevance
“…In Drosophila , Spz-4 and Spz-6, which are expressed in the late embryo, are involved in the antifungal response along with Toll 5 and development, respectively [ 25 , 26 ]. In T. molitor , Spz-4 is involved in the transcriptional regulation of AMPs, which modulate the humoral immune response against E. coli and C. albicans [ 9 ], whereas T. molitor Spz-6 protects the larvae against E. coli and S. aureus by positively regulating the expression of the AMPs Tenecin-2 and Tenecin-3 [ 11 ]. In this study, the full-length ORF sequence of TmSpz-like was identified and characterized using a molecular informatics approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Drosophila , Spz-4 and Spz-6, which are expressed in the late embryo, are involved in the antifungal response along with Toll 5 and development, respectively [ 25 , 26 ]. In T. molitor , Spz-4 is involved in the transcriptional regulation of AMPs, which modulate the humoral immune response against E. coli and C. albicans [ 9 ], whereas T. molitor Spz-6 protects the larvae against E. coli and S. aureus by positively regulating the expression of the AMPs Tenecin-2 and Tenecin-3 [ 11 ]. In this study, the full-length ORF sequence of TmSpz-like was identified and characterized using a molecular informatics approach.…”
Section: Discussionmentioning
confidence: 99%
“…The cysteine motif domain of Tm Spz-like comprises conserved cysteine residues involved in disulfide bond formation, while one cysteine was involved in dimerization. A cysteine knot domain at the C-terminus, a cleavage region, and a signal peptide region has been identified in Tm Spz-4 and Tm Spz-6 [ 9 , 11 ]. Spz isoforms identified from the crustacean L. vannamei contain the signal peptide region and a cysteine knot region for Toll binding [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analyses of the mealworm beetle, Tenebrio molitor ( T. molitor ) , have demonstrated similar fundamental mechanisms (Edosa et al . 2020a; Edosa et al . 2020b; Keshavarz et al .…”
Section: Introductionmentioning
confidence: 99%
“…TmDefensin‐1 and − 2 , have been used in our previous studies (Edosa et al . 2020a,b; Jo et al . 2017, 2019; Keshavarz et al .…”
Section: Introductionmentioning
confidence: 99%